PENGARUH KOMPETENSI PROFESIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASIONAL - Haryaka, 13.5202.0118 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the influence of "The Effect of Professional Competence andÂ Organizational Commitment to Teacherâs Performance with Organizational Cultures as aÂ Moderated Variabel".Â In this study population of 207 people, whereas samples taken as many as 136 people asÂ respondents purposive sampling method. Criteria UPT all public servants in the Department ofÂ Education and Culture District of Talun. Measurements using a Likert scale of 5 (five) alternativeÂ answers. Test instruments used are validity and reliability. While the test model used is theÂ coefficient of determination and F test (goodnes of Fit). Test this hypothesis using regressionÂ analysis.Â Based on the results of the study can be summarized as follows: (i) professionalÂ competence positive and significant impact on teacher performance, (ii) organizationalÂ commitment does not affect the performance of teachers, (iii) organizational culture positive andÂ significant impact on teacher performance, (iv) organizational culture does not moderate theÂ influence of professional competence working with teacher performance, and (v) organizationalÂ culture does not moderate the influence of organizational commitment to work with the teachersÂ performance.Keywords: Professional Competence, Organizational Commitment, Organizational Culture andÂ Performance Teachers.